the The Effect Of Barins Gym Exercises On Cognitive Development In Grup B Kindergarten : The Effect Of Barins Gym Exercises On Cognitive Development In Grup B Kindergarten - Habibi, MA (Mataram University, 2024)
The cognitive development of children is closely related to neural functioning. In this context, the effort to enhance a child's cognitive development necessitates the provision of brain stimulation. Among the activities designed to stimulate brain function, Brain Gym exercises have been reported as a promising method. Therefore, this study aimed to investigate the impact of Brain Gym exercises on cognitive development in Group B children. In this context, a quantitative approach was used with an experimental and Nonequivalent Control Group Design. The study population consisted of 23 Group B students at Kindergarten Lenterahati Islamic Boarding School. Sample selection was conducted using the Purposive Sampling technique and data collection included a statement-based test instrument that met the required quality standards. Meanwhile, data analysis was performed using an Independent Sample T-Test. The results showed that there was a significant difference (t -10.371, p 0.000 < 0.005) between Conventional Learning (M=44.50, SD=1.314), which exhibited lower cognitive abilities, and Brain Gym activities (M=50.45, SD=1.440). Therefore, Brain Gym exercises had an impact on the cognitive development of Group B children.